ANALISIS KEKUATAN TABUNG GAS LPG KAPASITAS 12 KG BERBAHAN CAST CARBON STEEL MENGGUNAKAN METODE ELEMEN HINGGA - Ahmad Saepuddin; Luchyto Chandra Permadi; Priyo Heru Adiwibowo (Steam Engineering, 2023)
Liquefied Petroleum Gas (LPG) is gas that is formed from the production of oil refineries and gas refineries. An energy source that is widely used in everyday life, especially in cooking and heating applications. The purpose of this study was to examine the strength performance of a 12 kg LPG gas cylinder in the face of external pressure that occurs during normal use. The method used in writing this scientific article is to review various literature and other references related to the analysis of the strength of LPG gas cylinders using SolidWorks software with the finite element method. The results of the analysis of the strength of the structure and the factor of safety obtained are the force test of 7.826e+03 and the theoretical value of 7.827.18385 does not exceed the yield strength value (2.482 x 105). After analysis, it is known that the smallest gas cylinder safety validation value is 1,1 and a maximum of 22.7, so that the material structure is safe and can be used to manufacture 12 kg LPG gas cylinders.